Faktor-faktor yang berhubungan dengan pemberian air susu ibu eksklusif di Kabupaten Sleman - Safitri Dwicahyani; Yayi Suryo Prabandari (Berita Kedokteran Masyarakat (BKM), 2017)
Determinants of exclusive breastfeeding in SlemanPurposeThe purpose of this paper was to determine the factors associated with the exclusive provision of breast milk in Sleman.MethodsA cross-sectional study was conducted using secondary data derived from HDSS Sleman Cycles I and II. The sample in this study were 218 mothers with children aged 7 to <24 months.ResultsThe ownership of health insurance and the use of bottles and pacifiers were significantly associated with exclusive breastfeeding. Maternal age, maternal education, and maternal occupation were not significantly associated with exclusive breastfeeding. Mothers with health insurance are 2.14 times more likely to exclusively breastfeed than those without health insurance. Infants who never use bottles, and pacifiers before the age of 6 months are 5.14 times more likely to receive exclusive breastfeeding than those who used bottles / dots before the age of 6 months.ConclusionThe use of bottles, and pacifiers is the most dominant factor associated with exclusive breastfeeding. Coverage of health insurance, especially in pregnant and lactating mothers and effective health promotion programs related to exclusive breastfeeding needs to be improved. HDSS Sleman needs to analyze the data more in-depth on exclusive breast-feeding.